Lindernia adami-hefiedi (Linderniaceae)—a new species from Madagascar - Fischer, Eberhard (Phytotaxa, 2023)
N/A The new species Lindernia adami-hefiedi from Madagascar, Montagne d’Ambre is described and illustrated. It differs from Lindernia rotundifolia, and related species in the dense indumentum with long-stalked glandular hairs, the matt leaves, the long pedicel, the large corolla and the long free staminodes. Additional material of the closely related species L. lemuriana, L. oblongifolia, L. rotundifolia and L. viguieri is studied and a key to the species of Lindernia s.str. in Madagascar is provided. Herbarium studies revealed that Ilysanthes oblongifolia is the oldest name for Lindernia paludosa, and the relevant new combination is made here.